Narrative Review : Update on Cardiogenic Shock and It's Management - Rahil Annisyah Putri D; Faisal Sommeng; Muhammad Asrul Apris; Nurhikmawati, Nurhikmawati; Muh. Nur Abadi (Jurnal EduHealth, 2024)
Cardiogenic shock is a condition of tissue hypoperfusion caused by primary abnormalities in the heart where there is a decrease in cardiac output, resulting in circulatory failure which results in hypoperfusion and tissue hypoxia. The most common cause of cardiogenic shock is acute myocardial infarction (AMI), of which 70% show a picture of ST-Elevation infarction (STEMI). The Society for Cardiovascular Angiography and Interventions (SCAI) has established five classifications of cardiogenic shock, namely A (At Risk), B (Beginning), C (Classic), D (Deteriorating), and E (Extreme). The main treatment that can be carried out in patients with cardiogenic shock is stabilizing the patient's oxygenation and circulation, then treating the underlying etiology of cardiogenic shock.